The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/1086296x19859516
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Plans for Writing: Characteristics and Impact on Writing Performance

Abstract: 2Planning plays an important role in the production of children's written texts. Yet little is 3 known about why children plan and the plans they create when they are not explicitly 4 instructed in planning activities. The current study explores the plans that elementary school 5 children create before writing a text. We compared performance of children educated in 6Catalan and in English (UK) to capture contextual differences and examined whether the 7 plans children produced were related to their language an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…The results of this study provide additional evidence that advance planning plays a significant role in CBM-WE performance as early as Grade 2 and that the role of advance planning is not completely shared by transcription. This finding is similar to some other studies of elementary students (Llaurado & Dockrell, 2019;Puranik et al, 2019), but in contrast to studies suggesting that planning is a higherlevel EF that does not develop until later (Drijbooms et al, 2015;Limpo et al, 2014). Given the lack of consensus and the inconsistent developmental arc we described in the introduction, we hypothesize that our result is due to capturing the right constructs in the right developmental stage.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of this study provide additional evidence that advance planning plays a significant role in CBM-WE performance as early as Grade 2 and that the role of advance planning is not completely shared by transcription. This finding is similar to some other studies of elementary students (Llaurado & Dockrell, 2019;Puranik et al, 2019), but in contrast to studies suggesting that planning is a higherlevel EF that does not develop until later (Drijbooms et al, 2015;Limpo et al, 2014). Given the lack of consensus and the inconsistent developmental arc we described in the introduction, we hypothesize that our result is due to capturing the right constructs in the right developmental stage.…”
Section: Discussionsupporting
confidence: 91%
“…The role of planning for young writers has been conditional on a variety of factors, including the representation of planning and its relation to transcription. Llaurado and Dockrell (2019) found that planning influenced writing length, fluency, and quality in a sample of Years 1, 3, and 5 students. Planning was scored based on structure (1–3 points) and content (0–3 points).…”
Section: Roles Of Planning In Early Writingmentioning
confidence: 94%
See 1 more Smart Citation
“…It is noteworthy that the vast majority of studies in this group focus on reading not writing, and that all studies reviewed confined their interest to the reading and writing of print text rather than multiple modes or media. The three studies that focus on writing trace the relative competence of children of different ages in writing certain text types (Tolchinsky, 2019;Stavans et al, 2019) and in planning for writing (Llaurado and Dockrell, 2019). In recent years, as explored earlier, some countries have expanded their literacy curricula to include skills associated with making and using multimodal and/or digital texts.…”
Section: Literacy As a Set Of Skills (55 Articles)mentioning
confidence: 99%
“…These few studies increase the need for a greater research effort to find out what the written communication problems of students with intellectual disabilities are in order to implement specific interventions tailored to their needs. However, the difficulty of analysing and fully understanding the global process of written composition and the relevance given to reflecting on writing (Hayes, 1996 ) made this research focus on the cognitive process of planning, considered as a central component of written expression (Llaurado & Dockrell, 2019 ; McCutchen, 2006 ).…”
Section: Introductionmentioning
confidence: 99%